MANAJEMEN RISIKO PROYEK PEMASANGAN ELEVATOR DI PT TERBANG JAUH: PROYEK WISATA PINUS BANDUNG - Melanie Kartika, Jennifer
PT Terbang Jauh (pseudonym) is a contractor company that procure, sale, install, and maintain elevator. In 2022, 64% of elevator installation project by PT Terbang Jauh experienced installation cost overrun with the average of 21%. According to Technical Manager and Finance Director of PT Terbang Jauh, this was caused by delay in installation that happened because of the occurrence of project risks and uncertainties that hinder the installation process. The company had tried to mitigate the risks by trial and error but the mitigation was not effective. Therefore in this research a structured project risk management was proposed for PT Terbang Jauh in order to minimize probability and/or impact of project risks so that the installation delay and cost overrun could be reduced or avoided. Wisata Pinus Bandung Project, which was an inclinator installation project, was choosen because of its riskier nature than normal vertical elevator installation. Risk management for Wisata Pinus Bandung Project was formed based on framework by PMI (2017, 2019, dan 2021) and Bissonette (2016). Firstly a risk management plan (RMP) was determined. Then project risks were identified and 157 process risks and seven strategic risks were obtained. Those risks were assessed by its probability and impact qualitatively. Then the severity rating of the risks were calculated. After that the risks were mapped to a risk matrix. Most of the risks (128 risks) were mapped to moderate severity category, which meant that the severity rating did not significantly affect project success. From the mapping process, six risks with high severity category that became the priority to be handled were also obtained. Those were process risks RP96 and RP150 about invoice billing delay, RP99 and RP153 about payment delay, RP117 about bad weather, and strategic risks RS4 about decreasing competitiveness compare to competitors. After that a quantitative analysis on overall project risk were done using sensitivity analysis. The range of variable type cost installation components that were still allowed (did not cause cost overrun more than 10% of cost installation) were obtained: working day variable could range between 54 to 60 days (followed by addition of overtime day a, overtime day b, and overtime day c) also to 61 days (followed only by addition of overtime day a), frequency of visitation variable could range between 48 to 912 times, and number of senior helper, helper, and day laborer variables could range between six to seven people, one to two people, and two to three people. After that plans to response seven risks with high severity individually and overall project risk were proposed. The type of the response plans were mitigate and accept. The economic impact caused by applying risk management for Wisata Pinus Bandung Project was decreasement of installation cost overrun that happened because of installation duration delay. This could be happened because project risk management were formed to minimize the probability and/or impact of risks that could delay the installation process. Therefore the company could increase its profit. But it was important to assess the comparison between the benefit and cost when applying the proposed project risk management. Meanwhile the social impact that could occure was establishment of an integrated work culture through formal risk review meetings at the beginning and end of the project so that the probability and/or impact of internal company management risks can be reduced.